Estudio de prefactibilidad para la instalación de un taller de servicios de carrocería y pintura express para vehículos livianos - Caceres Carranza, Renato Raul (2020)
The objective of the study is to demonstrate the technical, economic, financial, and social and market feasibility for the installation of a body and painting workshop with an express service in Modern Lima. The express service of the body and paint shop is aimed at serving vehicles with minor damage to be repaired in 24 hours. In Peru there are currently no specialized workshops in this service and there is a demand not met. The sector is served by multi-brand workshops, concessionaires and informal workshops; Our competence will be within the multi-brand workshops, catering to all light vehicles of any brand. It was determined that the demand for the year 2019 is 4 681 vehicles, and the projection towards the year 2023 is 5 351 vehicles; focused only on the NSE A and B of Modern Lima. It was determined that the workshop will be located in the district of Surquillo due to its proximity to the target public. The economic and financial evaluation show the feasibility of the body shop and painting installation: with a B / C ratio of 3,17, a TIR of 70%, a VAN of 1 203 191 and a Recovery Period of 1,56 years in the economic evaluation and a B / C ratio of 6,78, an IRR of 138%, a NPV of 1 284 222 and a recovery period of 0,77 years in the financial evaluation. The results of the social evaluation show the following: a capital density of 20 555,59 soles per employee, a capital intensity of 0,081 soles per employee and a capital product ratio of 12,28. So it is concluded that the installation of the workshop will benefit many users who currently do not have a service tailored to their requirements and will contribute to strengthen the aftermarket sector of the automotive market.